Impacto de las empresas transnacionales en los derechos humanos: de los acuerdos voluntarios a la resolución 26/9 de Naciones Unidas. - Moncada Landeta, Ketty Tamara. (2019)
In the globalization, transnational corporations are characterized by hold economic and political power that allows them to influence decision-making, at the state and international levels, to fulfill their objective: the accumulation of capital, without considering the negative consequences of the exercise of their activities on human rights and the environment. In this regard, there are some international instruments that prioritize the economic aspect about to the human rights, causing the configuration of a legal asymmetry that leaves victims helpless. In this context, civil society and few States have promoted the adoption of an international legal framework that regulates them. Therefore, in this research analyzes the impact and responsibility of transnational corporations infringement of human rights and the importance of transcending the voluntaries agreements to an international legally binding instrument, crystallized by Resolution 26/9 of United Nations.